2016
DOI: 10.1002/app.44644
|View full text |Cite
|
Sign up to set email alerts
|

Properties of poly(butylene adipate‐co‐terephthalate) and sunflower head residue biocomposites

Abstract: Utilization of low-value agricultural waste for polymer composite materials has great environmental and economical benefits. Sunflower head residue (SHR) as an agricultural waste may be used as a reinforcement in polymeric materials because of its fiber characteristics. In this work, composites of biodegradable poly(butylene adipate-co-terephthalate) (PBAT) and SHR were prepared via melt-extrusion compounding. To improve interfacial compatibility, maleic anhydride (MA) grafted PBAT (PBAT-g-MA) was prepared and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 44 publications
(54 reference statements)
0
28
0
Order By: Relevance
“…Compared with PBAT with the same copolymer composition, it can be observed that PBS 50 tBS 50 presents slightly higher σ y and ε b . 38 Aliphatic−aromatic copolyesters always gave higher stress compared to aliphatic copolyesters because the aromatic moiety endowed the copolyesters with stronger chemical rigidity. PBS 50 tBS 50 presented similar tensile properties with aliphatic−aromatic PBAT, which could be attributed to the improved crystallinity of PBS 50 tBS 50 in this composition range.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Compared with PBAT with the same copolymer composition, it can be observed that PBS 50 tBS 50 presents slightly higher σ y and ε b . 38 Aliphatic−aromatic copolyesters always gave higher stress compared to aliphatic copolyesters because the aromatic moiety endowed the copolyesters with stronger chemical rigidity. PBS 50 tBS 50 presented similar tensile properties with aliphatic−aromatic PBAT, which could be attributed to the improved crystallinity of PBS 50 tBS 50 in this composition range.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A very valuable agricultural product is sunflower seed (Helianthus annulus L.) from which edible oil and other nutritious foods are obtained [26]. However, after the industrial processing of sunflower seeds, their shells are considered as agricultural residues.…”
Section: Introductionmentioning
confidence: 99%
“…Because about 30% of the weight of a sunflower seed is the shell [27], millions of tons of sunflower seed shell residue result annually. The use of this low-value agricultural waste for the development of composite materials offers economic benefits and also contributes to the protection of the environment [26]. Powder from sunflower seed hulls can give the appearance of wood to polymer composites and can thus contribute to the conservation of forest resources.…”
Section: Introductionmentioning
confidence: 99%
“…As with other blends, it requires compatibilization for optimal mechanical properties 8 . One strategy is to graft PBAT with maleic anhydride (MA) using reactive extrusion in the presence of a peroxide initiator 2,8–16 . MA is one of the most widely used reactive compatibilizers due to its good chemical reactivity, low toxicity and low potential for homopolymerization.…”
Section: Introductionmentioning
confidence: 99%
“…8 One strategy is to graft PBAT with maleic anhydride (MA) using reactive extrusion in the presence of a peroxide initiator. 2,[8][9][10][11][12][13][14][15][16] MA is one of the most widely used reactive compatibilizers due to its good chemical reactivity, low toxicity and low potential for homopolymerization. It is mostly chosen for its ability to react with other polymers when the graft polymer is used as a compatibilizer in blends, especially polymers with functional groups such as -OH, -COOH, or -NH 2 .…”
Section: Introductionmentioning
confidence: 99%